Correction: Aromaticity and sterics control whether a cationic olefin radical is resistant to disproportionation. Issue 26 (29th June 2021) - Messelberger, Julian; Grünwald, Annette; Goodner, Stephen J.; Zeilinger, Florian; Pinter, Piermaria; Miehlich, Matthias E.; Heinemann, Frank W.; Hansmann, Max M.; Munz, Dominik
Abstract : Correction for 'Aromaticity and sterics control whether a cationic olefin radical is resistant to disproportionation' by Julian Messelberger et al., Chem. Sci., 2020, 11, 4138–4149, DOI: ; 10.1039/D0SC00699H .